2021
DOI: 10.7554/elife.73535
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the endogenous DAF-12 ligand and its use as an anthelmintic agent in Strongyloides stercoralis

Abstract: A prevalent feature of Strongyloides stercoralis is a life-long and potentially lethal infection that is due to the nematode parasite’s ability to autoinfect and, thereby, self-replicate within its host. Here, we investigated the role of the parasite’s nuclear receptor, Ss-DAF-12, in governing infection. We identified Δ7-DA as the endogenous Ss-DAF-12 ligand and elucidated the hormone’s biosynthetic pathway. Genetic loss of function of the ligand’s rate-limiting enzyme demonstrated that Δ7-DA synthesis is nece… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 48 publications
2
15
0
Order By: Relevance
“…The authors also suggested the improvement of the strategy by targeting both free-living males and females to improve the incidence of F1 homozygous knockouts [ 86 ]. Subsequent CRISPR/Cas9-mediated homozygous disruption methods have helped link some S. stercoralis -specific genes to functions involved in host infection (disruption of Ss-tax-4 severely affects positive thermotaxis toward host body temperatures) [ 88 ] and, recently, to development (disruption of DAF-12 and DIP-1 proteins are crucial for the developmental arrest and reactivation of infectious L3, respectively) [ 91 , 92 ].…”
Section: Advanced Techniques: Crispr/cas9mentioning
confidence: 99%
“…The authors also suggested the improvement of the strategy by targeting both free-living males and females to improve the incidence of F1 homozygous knockouts [ 86 ]. Subsequent CRISPR/Cas9-mediated homozygous disruption methods have helped link some S. stercoralis -specific genes to functions involved in host infection (disruption of Ss-tax-4 severely affects positive thermotaxis toward host body temperatures) [ 88 ] and, recently, to development (disruption of DAF-12 and DIP-1 proteins are crucial for the developmental arrest and reactivation of infectious L3, respectively) [ 91 , 92 ].…”
Section: Advanced Techniques: Crispr/cas9mentioning
confidence: 99%
“…Dafachronic acid detected in a few species of parasitic helminths (A. ceylanicum, A. suum, S. stercolis, H. contortus, and T. canis) is another example of a small molecule with therapeutic potential. When methylprednisolone acetated-treated NSG mice undergoing hyperinfection with S. stercolis were administered 10 mM dafachronic acid orally with drinking water, it significantly reduced the worm burden in mice (Patton et al, 2018;Wang et al, 2021). Although saturated fatty acids such as palmitic acid and stearic acid were detected in all bioactive extracts, SCFAs such as acetate, propionate, and butyrate could be responsible for the observed protection as Tedelind et al (2007) have reported anti-inflammatory properties associated to these SCFAs (Tedelind et al, 2007).…”
Section: Potential Application Of Small Molecules In Immunomodulatory...mentioning
confidence: 97%
“…Analogies have been made between the direct and indirect development of Strongyloides and the dauer versus non-dauer choice of free-living nematodes (including C. elegans ) [44], which have been explored for a range of parasitic nematodes including Strongyloides , though probably with little ultimate benefit [45,46]. However, recently it has been shown that Δ7-dafachronic acid specifies the development of S. stercoralis infective larvae, a mechanism that is directly analogous with C. elegans dauer larva development [47]. But there are also other levels of control that are not understood, for example how the sex of Strongyloides infective larvae is always female.…”
Section: Theme 1: Basic Biology and Immunologymentioning
confidence: 99%